The formation of spiritual values: Changes and evolutions - Boybekova Shahnoza Aliyevna (Review of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to examine the role of spiritual values in shaping development trajectories, determining social goals, and influencing ethical frameworks within the context of postmodern society. It emphasizes how spiritual values contribute to strengthening institutional systems and fostering creativity among the younger generation. Research/methodology: The research adopts a qualitative descriptive approach, synthesizing findings from global scientific literature, ethical philosophy, and institutional analysis. Content analysis is used to trace emerging trends in the study of spiritual values, while a comparative framework highlights their application across different cultural and scientific contexts. Results: Findings reveal that spiritual values increasingly serve as a guiding principle in the modernization of institutional systems. They play a crucial role in embedding respect for ethics, cultivating creative potential, and ensuring the sustainable transfer of cultural heritage to younger generations. The study also demonstrates how the integration of spiritual values enhances both individual growth and collective social stability. Conclusions: The research concludes that spiritual values are no longer peripheral but central to scientific inquiry and social development in postmodern society. Their recognition contributes to building cohesive communities and shaping innovative human resource strategies. Limitations: The study is conceptual in nature and relies heavily on secondary sources. Empirical evidence from diverse cultural contexts remains limited and requires further exploration. Contribution: This research enriches the discourse on ethics, culture, and development by framing spiritual values as a contemporary focus in modern science and institutional practice.